Prolonged cycling lowers subsequent running mechanical efficiency in collegiate triathletes - Stewart, J. A.; Merritt, E. K.; Lidstone, D. E.; McBride, J. M.; Zwetsloot, K. A. (BMC Sports Science, Medicine and Rehabilitation, 2022)
Background A significant challenge that non-elite collegiate triathletes encounter during competition is the decline in running performance immediately after cycling. Therefore, the purpose of this study was to determine if performing a 40-km bout of cycling immediately before running would negatively influence running economy and mechanical efficiency of running during simulated race conditions in collegiate triathletes.